Seasonality Anomalies Of Malaysia Revisited - Ching, Tan Voon (2007)
The calendar anomalies provide opportunity to te investors to generate tha abnormal return.This study examines the seven calendar anomalies, namely, the weekend effect,the February effect,the pre-UMNO effect, the pre-Budet effect and the post-Budget effect. The main objective of this study is to examine the existence of these seven calendars anomalies in Bursa Malaysia. The daily returns of KLCI and main board\'s stocks in Bursa Malaysia from January 1992 to September 2006 are taken as the raw data for this study.